The energy is in you - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Renewable energy has become mainstream. The weird and wacky appliances of the seventies now mean big business and big opportunities for small farmers and small processors. Whatever next?At the mouth of the port of Dakar in Senegal, a kilometre or...